The Universe at z > 10: predictions for JWST from the universemachine DR1. Issue 4 (14th October 2020) - Behroozi, Peter; Conroy, Charlie; Wechsler, Risa H; Hearin, Andrew; Williams, Christina C; Moster, Benjamin P; Yung, L Y Aaron; Somerville, Rachel S; Gottlöber, Stefan; Yepes, Gustavo; Endsley, Ryan
ABSTRACT: The James Webb Space Telescope ( JWST ) is expected to observe galaxies at z > 10 that are presently inaccessible. Here, we use a self-consistent empirical model, the universemachine, to generate mock galaxy catalogues and light-cones over the redshift range z = 0−15. These data include realistic galaxy properties (stellar masses, star formation rates, and UV luminosities), galaxy–halo relationships, and galaxy–galaxy clustering. Mock observables are also provided for different model parameters spanning observational uncertainties at z < 10. We predict that Cycle 1 JWST surveys will very likely detect galaxies with M * > 10 7  M⊙ and/or M 1500 < −17 out to at least z ∼ 13.5. Number density uncertainties at z > 12 expand dramatically, so efforts to detect z > 12 galaxies will provide the most valuable constraints on galaxy formation models. The faint-end slopes of the stellar mass/luminosity functions at a given mass/luminosity threshold steepen as redshift increases. This is because observable galaxies are hosted by haloes in the exponentially falling regime of the halo mass function at high redshifts. Hence, these faint-end slopes are robustly predicted to become shallower below current observable limits ( M * < 10 7  M⊙ or M 1500 > −17). For reionization models, extrapolating luminosity functions with a constant faint-end slope from M 1500 = −17 down to M 1500 = −12 gives the most reasonable upper limit for the total UV luminosity and cosmic star formation rate up to z ∼ 12. We compare to three other empirical models and one semi-analytic model, showing that the range of predicted observables from our approach encompasses predictions from other techniques. Public catalogues and light-cones for common fields are available online.